THE PROJECT-BASED ASSESSMENT LEARNING MODEL THAT IMPACTS LEARNING ACHIEVEMENT AND NATIONALISM ATTITUDES - Widiana, I Wayan; Tegeh, I Made; Artanayasa, I Wayan (LPMPP Universitas Negeri Yogyakarta, 2021)
Globalization gives a negative influence on children’s nationalism. This is exacerbated by the low students’ learning achievement in the social studies education (SSE), despite the fact that one of the objectives of the SSE learning is to develop students’ potentials to be sensitive to social problems in the person, the society, the nation, and the state. This study is aimed at describing the effectiveness of the project-based assessment learning model with national insight- oriented activities on the SSE learning achievement and nationalism attitudes of primary school students. The study is quasi-experimental research with a non-equivalent pre-test post test control group design. The research population consisted of all fourth-grade students totaling to 231 in number. Sampling was done by the random sampling technique, resulting in 46 students. Data were collected using test and non-test techniques. The test instrument was a multiple-choice test and the non-test instrument was a five-scale questionnaire. Both instruments were subjected to validity and reliability testing. The data analysis technique used the MANOVA statistic with the help of the SPSS computer software. The results showed that the significance level of the MANOVA test was .000 ( .0). This means that there are significant differences both partially and simultaneously in the SSE learning achievement and nationalism attitudes between students who learn by applying the project assessment learning model and students who learn ny applying the conventional learning model. In other words, there is a positive significant effect of learning using the project-based assessment learning model oriented on nationalism-insight activities towards the students’ SSE learning achievement and nationalism attitudes.